MARK-UP VS. INTEREST-BASED FINANCING ON GDP: AN APPLICATION OF AGENT-BASED COMPUTATIONAL MODEL - Diyah Putriani; Gairuzazmi Mat Ghani; Mira Kartiwi (Bank Indonesia, 2021)
This study aims to introduce the application of artificial intelligence in the area of Islamic finance by examining the dynamic changes of gross domestic product (GDP) under fully markup-based financing. The application of artificial intelligence using agent-based computational model (ABM) is employed to conduct the simulation. The simulation result shows that the movement of GDP under markup-based financing which represents Islamic financial system has better performance compared to interest-based lending. In this regard, profit shared to depositors has positive impact on GDP which also proofs that Islamic banking system may promote sustainable economic growth and may create wealth for the whole society. This study proofs that Islamic bank essentially more stable than conventional bank and hence may fights against crisis. This study is potentially the initial work to examine the dynamic changes of economic growth under fully Islamic financial system by applying artificial intelligence concept as its methodology. Thus, this study is expected to contribute to the development of Islamic economics and finance research.